Respuesta :

Answer:

[tex] \boxed{\sf (x + y)(6x + 5y)} [/tex]

Step-by-step explanation:

Factor the following:

[tex] \sf \implies 6 {x}^{2} + 11xy + 5 {y}^{2} [/tex]

The coefficient of x² is 6 and the coefficient of y² is 5. The product of 6 and 5 is 30. The factors of 30 which sum to 11 are 5 and 6.

So,

[tex] \sf \implies 6 {x}^{2} + (6 + 5)xy + 5 {y}^{2} [/tex]

[tex] \sf \implies 6 {x}^{2} + 6xy + 5xy + 5 {y}^{2} [/tex]

[tex] \sf \implies 6x(x + y) + 5y(x + y)[/tex]

Factor (x + y) from 6x(x + y) + 5y(x + y):

[tex] \sf \implies (x + y)(6x + 5y)[/tex]